PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN TINGKAT HUTANG TERHADAP TAX AVOIDANCE (Studi Kasus Pada Perusahaan Pertambangan yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023 - Triningsih, rizka adila; Andika, Arditya Dian; Ratnawati, Juli; Suhartono, Entot (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2025)
This study aims to analyse the effect of profitability, company size, and debt level on tax avoidance of mining companies on the indonesia stock exchange (IDX) during the period 2020-2023. The research uses a quantitative approach with secondary data obtained from the company's financial statements. The sample was determined by purposive sampling method, resulting in 131 observation data from 52 companies. The independent variables of this study include profitability as measured using ROA, company size as measured by the natural log of total assets, and debt level as measured by DER. The dependent variable is tax avoidance as measured by CETR. The analysis technique is panel data regression model using Eviews 12. The results showed that profitability, company size, and debt level do not have a significant influence on tax avoidance. This research contributes to the taxation and corporate finance literature, as well as being a reference for company management and policy makers. Keywords: tax avoidance, profitability, company size, debt level.